Direct observation of magnetic vortex behavior in an ordered La0.7Sr0.3MnO3 dot arrays. Issue 40 (3rd October 2016) - Li, Zhenghua; Dong, Dapeng; Liu, Dedi; Liu, Jia; Liu, Dongping; Li, Xiang
Abstract : Directly observing the magnetic domain behavior in patterned nanostructures is crucial to the investigation into advanced spin-based devices. Abstract : Directly observing the magnetic domain behavior in patterned nanostructures is crucial to the investigation into advanced spin-based devices. Herein, we show that the magnetic vortex behavior can be deterministically observed and controlled in highly spin polarized La0.7 Sr0.3 MnO3 (LSMO) triangular dots by successive in-field magnetic force microscopy (MFM). Imaging the magnetic domains with MFM shows that most of the LSMO dots exhibit magnetic vortex states with a clockwise or anticlockwise "pinwheel" structure for decreasing the demagnetization energy. Probing the vortex chirality using in-field MFM indicates that the selective spin circulation of the triangular dots depends on the magnetic orientation of the bias nanomagnet with specially designed geometries. Comparison between measurement and simulation reveals that the vortex behavior should be governed by an interface involved pinning strength at the boundaries, as well as a geometrically induced shape anisotropy of the triangular dot, both of which result in shape-dominated magnetic domain reversals.